2011
DOI: 10.1111/j.1600-0897.2011.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Aspects of Endometriosis: An Update

Abstract: Citation Olovsson M. Immunological Aspects of Endometriosis: An Update. Am J Reprod Immunol 2011; 66 (Suppl. 1): 101–104ProblemEndometriosis is a very complex disease that profoundly affects the quality of life of many women.Method of studyA review of the relationships between the female immune system and the occurrence and development of endometriosis.ResultsFunction and dysfunction of the female immune system plays important roles in the initiation and progression of the disease and its relation to infertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 41 publications
1
42
0
6
Order By: Relevance
“…In agreement with the results of previous studies, we also demonstrate that TNF-α stimulation promotes the activation of NF-κB and AP-1, critical regulators of cell proliferation and inflammatory responses in HESCs, suggesting that these transcription factors are key factors in the pathogenesis of endometriosis (3,14). The canonical pathway of NF-κB is activated in endometriotic lesions, and modulation of NF-κB activity and the consequent cell responses, including proliferation, inflammation and adhesion are important in the development of endometriosis (3,13,24,25).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In agreement with the results of previous studies, we also demonstrate that TNF-α stimulation promotes the activation of NF-κB and AP-1, critical regulators of cell proliferation and inflammatory responses in HESCs, suggesting that these transcription factors are key factors in the pathogenesis of endometriosis (3,14). The canonical pathway of NF-κB is activated in endometriotic lesions, and modulation of NF-κB activity and the consequent cell responses, including proliferation, inflammation and adhesion are important in the development of endometriosis (3,13,24,25).…”
Section: Discussionsupporting
confidence: 79%
“…The canonical pathway of NF-κB is activated in endometriotic lesions, and modulation of NF-κB activity and the consequent cell responses, including proliferation, inflammation and adhesion are important in the development of endometriosis (3,13,24,25). Thus, it is noteworthy that the present study demonstrated that HEABG significantly inhibits the TNF-α-induced activation of NF-κB and AP-1 in HESCs.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Учи-тывая, что эндометриоз является заболеванием, свя-занным с увеличением инфламаторной активности в брюшной полости, на брюшине и в эутопическом эндометрии, эти изменения объективно снижают шанс наступления беременности [35] и, следователь-но, полученные результаты вполне объяснимы. Тем не менее у обследованных больных отсутствовали Основные иммуногистохимические характеристики фенотипических особенностей эутопического эндометрия у боль-ных с перитонеальной формой эндометриоза в зависимости от наступления беременности.…”
Section: Discussionunclassified